Study on Acquisition of Japanese Adnominal Clauses Using Metalanguage Awareness in Indonesian Learners - Maarif, Samsul (JAPANEDU: Jurnal Pendidikan dan Pengajaran Bahasa Jepang, 2021)
The theoretical research of Japanese linguistics is diverse. However, applying such research theory to Japanese language education does not necessarily help learnersâ€™ understanding. The purpose of this research is to concretely present the problems that arise from the gap between theory and practice in Japanese language research and Japanese language education. In this study, we examine the effect of the theoretical explanation of the Japanese adnominal clause on the learnersâ€™ understanding. We selected 10 second-year university Japanese learners as research subjects. They were selected because second-year learners already learn the adnominal clause. The adnominal clause was chosen because it has a considerably simple construction to check whether the learners can comprehend the meaning from those simple constructions. Since the theoretical explanation of linguistics is difficult for learners to understand, we gave a lesson using the learnersâ€™ awareness of language called â€œmetalanguage awareness.â€ By using metalanguage awareness, learners are guided to understand the meaning through the comprehension of its grammatical construction using linguistic terms both in Japanese and their native language, which is Indonesian. As a result, it was found that even though adnominal clause construction is simple, the understanding of the meaning is not that simple. The understanding of adnominal clauses depends on the understanding of more basic learning items of â€œparticlesâ€ and â€œclausesâ€, which learners still canâ€™t grasp. We conclude that introducing such dependency in focus on form teaching method has the advantage for the teacher to check the degree of learnersâ€™ understanding. In this study, the adnominal clause can be used to check whether learners have fully understood the concept and usage of â€œparticlesâ€ and â€œclausesâ€ in Japanese. Since both concepts are very basic, it is important to take a step back and re-explain both concepts and usage so learners can use them correctly in the future.